Predicting the unpredicted … brain response: A systematic review of the feature-related visual mismatch negativity (vMMN) and the experimental parameters that affect it. - Alie G Male (PLoS ONE, 2025)
In this systematic review and meta-analysis, I consider aspects of experimental design that affect the visual mismatch negativity (vMMN)-an electrophysiological (neural) correlate of prediction error in vision that is typically largest between 150 ms and 300 ms in the event-related potential (ERP) at occipito-parietal regions on the scalp. I compiled data from 145 published studies investigating changes in a single property or feature of visual input. This review provides a concise summary of the vMMN literature on unexpected changes in features of visual input, outlining the most used (according to review) and optimal (following discussion on theoretical and practical implications) parameters of experiments investigating feature deviance for posterity as well as contemporary research. The data compiled was analysed to reveal meaningful relationships between aspects of experimental design and vMMN mean amplitude and peak latency. Results suggest that whether a control for adaptation is used, whether attention is towards vs. away from the stimulus of interest, and stimulus presentation time determines mean amplitude. Whether attention is towards vs. away from the stimulus of interest, the time between the stimulus of interest, deviant probability, and the number of standards separating deviants determines peak latency. There is also some indication that magnitude of deviance affects mean amplitude in studies exploring orientation deviance. This review and its findings elucidate potentially fruitful areas of future research.